Fifty years of BMT: risk stratification, donor matching, and stem cell collection for transplantation - Salhotra, Amandeep; Yuan, Shan; Ali, Haris (Frontiers in Oncology, 2023)
In this review we discuss recipient risk assessment for allo-HCT with regards to comorbidities present at baseline to predict non relapse mortality. We further review the incorporation of remission status plus cytogenetic risk prior to allo transplant to predict relapse rates for hematologic malignancies. The HCT-CI and DRI are tools available to physicians to assess risk- benefit of allo-HCT in patients referred for transplantation. We next discuss our algorithm for donor selection and criteria for donor selection in case matched donors are not available. Finally, we discuss our approach for stem cell mobilization especially in donors failing G-CSF and our approach for use of plerixafor and data supporting its use.